The facial nerve injury after temporomandibular joint surgery after endaural approach with sharp dissection (2021)
Several authors have extensively modified approaches to temporomandibular joint surgery throughout history to improve access, improve aesthetics, and decrease the risk of nerve damage. However, This is why this retrospective cross-sectional is carried out to show the rate of facial nerve injury after the endaural approach with sharp dissection for the temporomandibular joint with a low rate of facial nerve paresis our case series.